The value of history. Study of curricular alternatives at secondary school (3): learning to think from multiple perspectives - Paricio Royo, Javier (Clio. History and History Teaching, 2020)
As a curricular orientation, discussing multiple perspectives on past events is as accepted among researchers as it is rare in our history classrooms. Following the trail of previous issues in this series of articles, this curricular orientation is analysed here in the light of published experiences and research, trying to clarify what it consists of, its keys, its most common practices and why it is valuable for students. Multiperspectivity is at the very core of history as a discipline. It is opposed to memory, characterised by closed stories that impose a single version of the past. In this tension between discipline and memory, the practice of history teaching has usually opted for the latter. But learning to analyse, evaluate and debate the different interpretations of the world of the past (and the present) has much more curricular value. Multiperspectivity not only means understanding the true controversial, open, and critical nature of history, but it is the very foundation of democratic citizenship.
Keywords: multiperspectivity, historical perspectives, controversial history, historical thinking, curricular studies, Secondary School History